Understanding the Essence of Class Culture in Building the Pancasila Learner Profile: An Approach to Quality Education - Robiultsani, Abdillah Rosyid; Budiyanto, Cucuk. Wawan; Siyamtiningtyas, Yuliyani (Universitas Sebelas Maret, 2023)
This study uses a descriptive qualitative approach to explore the essence of classroom culture in shaping the profile of Pancasila learners in class XI PPLG at one of the state vocational schools in Surakarta. Through participatory observation and in-depth interviews, teachers have been shown to play a central role in integrating national values, such as the habit of praying, giving advice, and creating a learning environment that supports learners' social development. Practices such as cooperation activities, group sharing for presentations, and giving learners the freedom to be independent became an integral part of the classroom culture. The results show positive developments in learners' tolerance towards different religions and opinions. The conclusion of the study confirms the importance of a deep understanding of classroom culture as the main key to creating quality education, which not only transfers knowledge but also shapes learners' characters into a generation with intelligence, character, and personality.